2021
DOI: 10.3390/met11121949
|View full text |Cite
|
Sign up to set email alerts
|

Tool Downscaling Effects on the Friction Stir Spot Welding Process and Properties of Current-Carrying Welded Aluminum–Copper Joints for E-Mobility Applications

Abstract: According to the technical breakthrough towards E-Mobility, current-carrying dissimilar joints between aluminum and copper are gaining an increasing relevance for the automotive industry and thus, coming into focus of many research activities. The joining of dissimilar material in general is well known to be a challenging task. Furthermore, the current-carrying joining components in E-Drive consist of pure aluminum and copper materials with relatively thin sheet thickness, which are thermally and mechanically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The max. spindle torques M ̂z for μFSSW were generally very low (3 to 10 times lower than for FSSW [19]), ranging from 0.44 Nm ± 0.03 Nm (tool 1) to 0.69 Nm ± 0.04 Nm (tool 2) for aluminium and from 0.80 Nm ± 0.04 Nm (tool 2) to 1.02 Nm ± 0.05 Nm (tool 1) for copper with generally very low CV for both tools (aluminium: 6-7%, copper: 5%). No trend or significant correlation could be detected for the max.…”
Section: Temperatures In the Weld Surrounding Areas (R5)mentioning
confidence: 90%
See 1 more Smart Citation
“…The max. spindle torques M ̂z for μFSSW were generally very low (3 to 10 times lower than for FSSW [19]), ranging from 0.44 Nm ± 0.03 Nm (tool 1) to 0.69 Nm ± 0.04 Nm (tool 2) for aluminium and from 0.80 Nm ± 0.04 Nm (tool 2) to 1.02 Nm ± 0.05 Nm (tool 1) for copper with generally very low CV for both tools (aluminium: 6-7%, copper: 5%). No trend or significant correlation could be detected for the max.…”
Section: Temperatures In the Weld Surrounding Areas (R5)mentioning
confidence: 90%
“…Afterwards (third step), the tool is retracted (retract speed vr), thereby leaving a characteristic negative imprint and flash on the surface. The process is highly automated and is typically monitored by using inline measured signals of the axial force Fz and the spindle torque Mz (process variables) [18][19][20]. A recent study [21] revealed the high potential of the process for cell-internal contacting.…”
Section: Introduction and State Of The Artmentioning
confidence: 99%